STOMATITIS IS AN INFLAMMATORY PROCESS OF THE ORAL MUCOSA - Rasulova Mohigul Matyokub kizi (TADQIQOTLAR, 2025)
Abstract: Stomatitis is an inflammatory process of the oral mucosa caused by the immune system's reaction to an irritant from the external environment. It manifests itself as swelling, redness and ulcers on the walls of the mucous membranes. This disease requires immediate treatment. If you delay, you cannot do without antibiotics, stomatitis spreads to healthy tissues. In addition, the patient cannot eat food calmly, he is bothered by a burning sensation, painful sensations when chewing food and talking.